Lung function dynamics in smoking and non-smoking patients with stable effort angina, treated with beta-adrenoblockers - Yu. V. Lukina; S. Yu. Martsevich; N. P. Kutishenko; S. A. Shalnova; O. V. Vikhireva (Российский кардиологический журнал)
.